Pipeline unburial behaviour in loose sand - Schupp, J; Byrne, B; Eacott, N; Martin, C; Oliphant, J; Maconochie, A; Cathie, D; ASME (2006)
Small diameter pipelines are routinely used to transport oil and gas between offshore production plants and the mainland, or between remote subsea well-heads and a centralised production facility. The pipelines may be placed on the soil surface but it is more usual that they are placed into trenches, which are subsequently backfilled. For the buried pipelines a well established problem has been that of upheaval buckling. This occurs because the fluid is usually pumped through the pipes at elevated temperatures causing the pipeline to experience thermal expansion which, if restrained, leads to an increase in the axial stress in the pipeline possibly resulting in a buckling failure. A secondary phenomenon that has also been identified, particularly in loose silty sands and silts, involves floatation of pipelines through the backfill material, usually shortly after burial. At the University of Oxford a project sponsored by EPSRC and Technip Offshore UK Ltd has commenced to investigate in detail the buckling and floatation problems. The main aim of the research programme is to investigate three-dimensional effects on the buckling behaviour. The initial experiments involve the more typical plane strain pipeline unburial tests to explore the relationship between depth of cover, uplift rate, pipeline diameter and pullout resistance under drained and undrained conditions. The second and main phase of experiments involves inducing a buckle in a model pipeline under laboratory conditions and making observations of the pipe/soil response. This paper will describe the initial findings from the research including a) plane strain pipe unburial tests in loose dry sand, and, b) initial small scale three-dimensional buckling tests. The paper will then describe the proposed large scale three-dimensional testing programme that will be taking place during 2006 and 2007. Copyright © 2006 by ASME.